Performance and Noise Prediction of Marine Propeller Using Numerical Simulation - Agung Purwana; I Made Ariana; Dhimas Widhi Handani; Wisnu Wardhana (Institut Teknologi Sepuluh Nopember, 2018)
One of the phenomenon appears on operation of marine propeller is noise. It could reduce performance of the propeller. In this study, numerical simulation is used to predict hydrodynamic performance and noise around non cavitation propellers. The formulation of RANS (Reynold Averaged Naiver Stokes) with turbulence model k-ω SST (Shear Stress Transport) and FWH (Ffowcs Williams–Hawkings formulation) is applied on the simulation. The noise is expressed in time-domain acoustic analogy as well as finite volume, and it is predicted at different receiver positions. The performance of propeller is predicted by MRF technique (Multiple Reference Frame). The 3D model of B-series propeller with diameter of D = 250 mm, blade number Z = 4, pitch diameter ratio P/D = 1, and area ratio Ae/Ao = 0.55 is simulated on various advance coefficients (J). Propeller rotation is simulated in range of 7.5 rps - 29rps and Re = 6.95x104– 3.36x106